Structural Analysis And Stilistic Meaning Of Khabariyah Verses In The Qur'an - Agustiar Agustiar; Khairunnas Jamal (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Al-Qur'an always displays the style of language in various forms. The diversity of the structure and language style of the Qur'an shows that there is a certain meaning that is displayed behind the text of the verse. This article aims to reveal the forms of linguistic structures and meanings contained in the khabariyyah verses in the Qur'an so that they can provide an alternative understanding of the Qur'an that does not favor one group. And can provide a clear understanding of meaning, open as it is in accordance with the form of a typical sentence structure in the form of speech and the meaning contained in it.The method used is Linguistic Theory by collecting the configuration of kalam khabariyyah then analyzing its structure and meaning through the Syntact and semantic analysis approach in the Qur'an interpretation. This article concludes that the configuration of the stylistic structure of the verses with khabariyyah style in the Qur'an is expressed in two constructions, namely in the construction of the Jumlah ismiyyah and Jumlah fi'liyyah with various kind of its language style (uslub) there are : in the style of uslub al-Qashru, al-Taqdim wa al -Takhir, and al-Qasam. In terms of meaning, it shows that the Jumlah ismiyyah provides the permanent (Itsbat),eternal (Dawam) and continuous meaning (istimrar), while the Jumlah fi'liyyah provides the occurrencemeaning (Huduts) that means the occurrence of an event at a certain time as well as the meaning of repetition (istimrar tajaddud)